Pendampingan Literasi Multidimensional dalam Meningkatkan Kemampuan Membaca, Numerasi, Sains, dan Sosial Budaya Peserta Didik di MAS Daruth Thalibin Bangilan - Ahmad Muzakki; Febrian Nafisa Nurul Afida; M. Yusuf Aminuddin (Journal of Innovation and Contribution to Community Service, 2025)
This assistance aims to identify and analyze the level of literacy skills of students in madrasas, which include reading literacy, numeracy literacy, scientific literacy, and socio-cultural literacy. The method used in this research is the Participatory Action Research (PAR) approach with a descriptive design. Data was obtained through test results reports given to students at Madrasah Aliyah Daruth Thalibin. The results of the mentoring show that overall, students' reading literacy skills are classified as proficient (good), but they still need to be improved so that students can understand more complex texts. Numeracy literacy shows varied results, with most students having sufficient basic understanding, but lacking in applying mathematical concepts to everyday problems. It is hoped that this research will provide an overview of the challenges and potential that students have in dealing with various types of literacy, as well as provide recommendations for developing a more comprehensive curriculum in madrasah.